Empowerment of Durian and Strawberry Farmers Through Digital Marketing and Low-Sugar Processing Innovation - Nurani Rahmania; Akmalia Fitri Mafaza (Bisma : Bimbingan Swadaya Masyarakat, 2025)
This community service program addresses the critical challenges faced by durian and strawberry farmers in Wonosalam, Jombang, namely significant post-harvest losses of non-premium grade fruit, dependency on middlemen leading to price suppression, and a lack of product diversification. The primary objectives were to enhance farmers’ capacity in low-sugar fruit processing, build their digital marketing literacy, and integrate these skills to increase added value and market competitiveness. Employing a Participatory Action Research (PAR) methodology underpinned by an Asset-Based Community Development (ABCD) approach, the six-month intervention involved 25 core farmers in a cycle of asset mapping, co-designing workshops on product processing (low-sugar jam, puree, chips) and digital marketing (WhatsApp Business, Instagram), and intensive mentoring. The results demonstrated a successful increase in practical skills and knowledge, the establishment of active online business profiles attracting over 2,300 followers, the generation of additional household income averaging IDR 285,000 from processed products, and enhanced group collaboration. The program concludes that an integrated strategy combining value-adding technology with digital market access, rooted in participatory empowerment and leveraging local assets, is an effective model for transforming farmers into market-savvy agripreneurs, offering a replicable blueprint for similar horticultural communities seeking sustainable economic improvement.